Penegakan Hukum terhadap Tindak Pidana Kekerasan pada Putusan Nomor 67/Pid.B/2020/PN.Liwa - B, Erlina; Anggalana, Anggalana; Wayguna, Candra (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2023)
Violent crime is a social problem that is always interesting and demands serious attention from time to time. The problems in this article are related to why one person is capable of committing a crime against another and what kind of legal sanctions should be imposed on the perpetrator based on the focus of the study on decision Number 67/Pid.B/2020/PN.Liwa. The research method used is a normative approach. The cause of the occurrence of criminal acts of violence against people in the case of decision Number 67/Pid.B/2020/PN.Liwa is because the perpetrators cannot control their emotions, causing violent crimes against other people. The perpetrator admitted his guilt through a trial which was proven by the public prosecutor through Article 170 paragraph 1 which was legally proven that the perpetrator was proven guilty. The perpetrator was sentenced to imprisonment by a panel of judges for five years and six months. ___ Referensi Buku dengan penulis: Soekanto, Soerjono., dan Mamudji, Sri. (2001). Penelitian Hukum Normatif: Suatu Tinjauan Singkat. Jakarta: PT Radja Grafindo Persada. Zainuddin. (2018). Metode Penelitian Hukum. Jakarta: Sinar Grafika. Willihardi, A. P. (2020). Analisis Yuridis Perlindungan Hukum bagi Korban Penyebarluasan Konten Pornografi dengan Motif Balas Dendam (Revenge Porn) di Indonesia. Surabaya: UPN Veteran Jawa Timur. Wiyata, A. L. (2002). Carok; Konflik Kekerasan & Harga Diri Orang Madura. Yogyakarta: LKiS Pelangi Aksara. Artikel jurnal: Arliman, L. (2019). Mewujudkan Penegakan Hukum yang Baik di Negara Hukum Indonesia. Dialogia Iuridicia: Jurnal Hukum Bisnis dan Investasi, 11(1), 1-20. Andini, T. M. (2019). Identifikasi Kejadian Kekerasan pada Anak di Kota Malang. Jurnal Perempuan dan Anak, 2(1), 13-28. Aryani, E., dan Triwanto, T. (2021). Penyuluhan Hukum tentang Kenakalan Remaja dan Penanganannya. Empowerment: Jurnal Pengabdian Masyarakat, 4(3), 248-253. Bangki, J. (2014). Perlindungan Hukum terhadap Anak di Bawah Umur Pemakai Narkoba. Lex et Societatis, 2(8), 110-117. Basuki, A. (2011). Pertanggungan Jawab Pidana Pejabat atas Tindakan Mal-Administrasi dalam Penerbitan Izin di Bidang Lingkungan. Perspektif, 16(4), 252-258. Benuf, K., dan Azhar, M. (2020). Metodologi Penelitian Hukum sebagai instrumen Mengurai Permasalahan Hukum Kontemporer. Gema Keadilan, 7(1), 20-33. Dewi, P. Y. (2020). Pengaruh Terpaan Adegan Kekerasan Dalam Game Online terhadap Sikap Agresifitas Remaja. Jurnal Ilmu Komunikasi, 11(3), 270-278. Effendi, R., Salsabila, H., dan Malik, A. (2018). Pemahaman tentang Lingkungan Berkelanjutan. Modul, 18(2), 75-82. Hartono, B., dan Aprinisa, A. (2021). Implementasi Sanksi Pidana Pelaku Tindak Pidana Kejahatan terhadap Nyawa Orang Lain yang Direncanakan (Pembunuhan Berencana). Jurnal Penelitian & Pengkajian Ilmiah Mahasiswa (JPPIM), 2(4), 31-44. Hufad, A. (2003). Perilaku Kekerasan: Analisis menurut Sistem Budaya dan Implikasi Edukatif. Mimbar Pendidikan, 22(2), 52-61. Oktalisa, Y. (2016). Analisis Yuridis Konsep Pertanggungjawaban Pidana terhadap Pembunuhan Berencana yang Dilakukan Anak Dibawah Umur. Justicia Sains: Jurnal Ilmu Hukum, 1(2), 61-70. Qodir, Z. (2012). Peran Negara dan Agama Dalam Memerangi Terorisme. Jurnal Orientasi Baru, 21(1), 93-108. Tazkiyah, N., dan Silaen, S. M. J. (2020). Hubungan Kecemasan dan Kecerdasan Emosional dengan Kecenderungan Perilaku Agresivitas Anak Jalanan di Sekolah Master Indonesia Depok. Ikra-Ith Humaniora: Jurnal Sosial Dan Humaniora, 4(2), 1-13. Wahyutomo, M. D. H. (2021). Pembelaan Diri yang Mengakibatkan Hilangnya Nyawa Orang Lain. Jurnal Mitra Manajemen, 5(12), 847-862. Yulianto, I. (2017). Kejahatan Percobaan Pembunuhan Dalam Hukum Pidana. FENOMENA, 15(1), 1528-1537.